First principle study of the conductive type stability in Sn, Li and Li-Ni doped ZnO nanosheet - Supatutkul C. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this study, the Sn, Li and Li-Ni doped ZnO nanosheet were studies using density functional theory implemented in Quantum espresso package. The electrical and optical properties of these doping effects on ZnO nanosheet were studied using Heyd-Scuseria-Ernzerhof (HSE) hybrid functional. The dopant ions were substituted on Zn sites in hexagonal ZnO nanosheets. The results showed that, for the n-type doping, the Sn-doped ZnO nanosheet is the most stable under O-poor condition compared with the Li doping and Li-Ni co-doping and has donor level at 2.29 eV below conduction band minimum (CBM). On the other hand, for the p-type doping, Li-doped ZnO nanosheet has acceptor level at 0.68 eV above valence band maximum (VBM) and is more energetic favorable than the Li-Ni doped ZnO in O-poor condition. Therefore, this density functional investigation shows that the high stability of ZnO nanosheets can be achieved for both p-type and n-type conductivity depending on the designed growth condition. These results then suggest the possibility to produce both conductive types in ZnO nanosheet for implementation as p-n junction in miniaturized electronics devices.